Worship of coconuts in a Koli household - Mumbai Archive Project Team (Jio Institute, 2024)
Coconuts are worshipped in a shrine at the Koli household before commencing auspicious ceremonies. The coconut holds significant cultural and religious importance in the Koli community and is used on all auspicious occasions. Its three eyes symbolize the Trimurti - the Hindu trinity of Brahma (the creator), Vishnu (the preserver), and Shiva (the destroyer).